Well-being Paradigm in the Context of Green Economy and Information Society; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 19 : Lifelong Wellbeing in the World (WELLSO 2016) - Egorova M. S. Mariya Sergeevna; Guzyr V. V. Vladimir Vasilievich; Cherdanceva I. V. Irina Vasilevna; Shatova M. Maria (2017, 2017)
Title screen